Quality of translation via google translate in comedy texts - Bania, Allif Syahputra; Faridy, Najihatul (Englisia: Journal of Language, Education, and Humanities, 2023)
A translation process of considerable quality should possess the ability to effectively communicate a clear and definite meaning from the source language to the target language. While Google Translate serves as a useful tool for comprehending translated textual content in a general sense, it is important to note that automated machines still possess inherent weaknesses and limitations. The translation of jokes within comedic texts, particularly in relation to language and cultural differences, proves to be a challenging task. This research was undertaken utilizing a qualitative-descriptive approach, with the bilingual comedy book titled "Jokes in English-Book 1" serving as the subject of study. The primary objective of this research is to assess the level of translation quality achieved by machine translation in terms of accuracy, acceptability, and readability, and to compare these results with the translations provided in the bilingual book. The findings of this research indicate that 62.5% of the translations exhibit a high level of accuracy, while 37.5% are somewhat less accurate. Furthermore, 37.5% of the translations are deemed acceptable, while 62.5% are regarded as less acceptable. Finally, 37.5% of the translations demonstrate a high degree of readability, whereas 62.5% exhibit a moderate level of readability. Upon comparing the translation results obtained from Google Translate with the original translations presented in the bilingual book, it was determined that 100% of the translations in the book were found to be satisfactory in terms of accuracy, acceptability, and readability. Although the translations from English to Indonesian of comedy texts via Google Translate are deemed satisfactory, there is still room for improvement and ongoing development in order to enhance the quality of these translations.